A crack templated copper network film as a transparent conductive film and its application in organic light-emitting diode - Ping Liu; Bing Huang; Lei Peng; Liming Liu; Qingguo Gao; Yuehui Wang (Scientific Reports, 2022)
Abstract In this paper, a highly transparent, low sheet resistance copper network film fabricated by a crack template, which made by drying an acrylic based colloidal dispersion. The fabricated copper network film shows excellent optoelectronic performances with low sheet resistance of 13.4 Ω/sq and high optical transmittance of 93% [excluding Polyethylene terephthalate (PET) substrate] at 550 nm. What’s more, the surface root mean square of the copper network film is about 4 nm, and the figure of merit is about 380. It’s comparable to that of conventional indium tin oxide thin film. The repeated bending cycle test and adhesive test results confirm the reliability of the copper network film. As a transparent conductive film, the copper network film was used as an anode to prepare organic light-emitting diode (OLED). The experiment results show that the threshold voltage of the OLED is less than 5 V and the maximum luminance is 1587 cd/m2.